2021
DOI: 10.32807/jkt.v3i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisitik Keluarga Pasien Tuberculosis Paru Di 5 Puskesmas Kabupaten Ende, Indonesia

Abstract: Peningkatan jumlah tenaga dan fasilitas kesehatan tersebut bukan menjadi jaminan kasus penularan TB paru dapat diturunkan secara signifikan. Selain pengobatan yang dilakukan secara total kepedulian keluarga terhadap anggota keluarga yang menderita TB paru menjadi salah satu cara menekan penularan TB paru. Tujuan penelitian ini adalah untuk memberikan gambaran karakteristik keluarga klien dengan kasus TB paru. Penelitian ini merupakan penelitian deskriptif analisitik dengan pendekatan survei. Populasi adalah ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, this study is also supported by research related to the impact of health education on preventing disease transmission to patients. This study states that the implementation of health education has an effect on transmission-prevention behaviour in the patient's family (Budiana et al, 2021;Mardila et al, 2023). The advantage of this study is that it uses audiovisual media that supports the implementation of health education for families caring for TB patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study is also supported by research related to the impact of health education on preventing disease transmission to patients. This study states that the implementation of health education has an effect on transmission-prevention behaviour in the patient's family (Budiana et al, 2021;Mardila et al, 2023). The advantage of this study is that it uses audiovisual media that supports the implementation of health education for families caring for TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Bali Provincial Health Office (2020), Denpasar City is in first place with the largest number of tuberculosis cases in Bali Province, namely (1,054 cases). The results of a preliminary study conducted by the author at the Denpasar City Health Office found that the highest tuberculosis cases occurred in West Denpasar, namely in the working area of the UPTD Puskesmas II West Denpasar with a total 353 cases (Budiana et al, 2021;Fitriana & Maryati, 2021). The role of the family in assisting tuberculosis patients is expected to help achieve the recovery rate so that the reduction in the number of tuberculosis patients can be achieved (Manik et al, 2020;Zakariya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%